2003
DOI: 10.1046/j.1471-4159.2003.02071.x
|View full text |Cite
|
Sign up to set email alerts
|

Puromycin selectively increases mdr1a expression in immortalized rat brain endothelial cell lines

Abstract: The blood-brain barrier (BBB) plays an important role in controlling the passage of molecules from blood to brain extracellular fluid. The multidrug efflux pump P-glycoprotein (P-gp) is highly expressed in the luminal membrane of brain endothelium and contributes to the formation of a functional barrier to lipid-soluble drugs such as anticancer agents. The mdr1a P-gp-encoding gene is exclusively expressed in the rodent BBB. Primary cultures of rat brain endothelial cells and GP8.3 cells showed a dramatic decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 38 publications
(61 reference statements)
0
13
0
Order By: Relevance
“…There are two isoforms of the mdr1 gene in rodents: mdr1a and mdr1b. Both forms are present in primary cultured rodent brain microvessel endothelial cells and immortalized brain endothelial cells [32, 33]. Our recent studies by microarray and real-time PCR have shown that mdr1b is highly expressed and shows stronger upregulation by TNF in both mouse cerebral microvessels and cultured RBE4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are two isoforms of the mdr1 gene in rodents: mdr1a and mdr1b. Both forms are present in primary cultured rodent brain microvessel endothelial cells and immortalized brain endothelial cells [32, 33]. Our recent studies by microarray and real-time PCR have shown that mdr1b is highly expressed and shows stronger upregulation by TNF in both mouse cerebral microvessels and cultured RBE4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of intra-endothelial cyclic AMP and stimulation of protein kinase C were shown to increase Pgp activity in GP8 cells (Deli et al, 2001). Also, chronic treatment of GP8 and GPNT cells with the selective agent puromycin was found to increase Pgp expression and activity with a selective increase in mdr1a mRNA expression (Demeuse et al, 2004). (1) Gomes and Soares-da-Silva, 1999;…”
Section: Use Of Immortalized Rbe Cell Lines For the Study Of Blood-brmentioning
confidence: 98%
“…Capillary fragments were directly seeded onto Falcon inserts (3-m pore; Fisher Scientific) coated with collagen type IV/ fibronectin (10 g/ml; Sigma-Aldrich) in DMEM with 10% FBS (Fisher Scientific), 2 mM L-glutamine, 100 U/ml penicillin, 100 g/ml streptomycin, and 50 g/ml gentamicin (Sigma-Aldrich). Isolated capillaries were cultured for 2 days in puromycin-supplemented medium (4 g/ml; SigmaAldrich) to eliminate contaminating perivascular smooth muscle cells, followed by culture in medium supplemented with basic fibroblast growth factor (2 ng/ml; Roche) (40,41). After reaching confluence, cells were cultured in serum-free DMEM/Ham's F12 (Sigma-Aldrich) containing 2 mM L-glutamine, 100 U/ml penicillin/streptomycin, and 50 g/ml gentamicin (Sigma-Aldrich) supplemented with hydrocortisone (550 nM; SigmaAldrich) (32).…”
Section: Brain Capillary Endothelial Cells (Bcec)mentioning
confidence: 99%